ANALISIS PREDIKSI KEBANGKRUTAN PERUSAHAAN DENGAN MENGGUNAKAN METODE ALTMAN Z-SCORE PADA PERUSAHAAN PENERBANGAN BERTARIF MURAH - Nasa Alkalas (Parsimonia - Jurnal Ekonomi dan Bisnis, 2016)
This research has the objective as the first step to knowing the company’s bankruptcy signal. Before we knowing it is certainly a company will meet bad financial health condition, so the chosen method is to use the model analysis of Altman Z-Score because uses data obtained from the financial reports and processed as a measure of the financial health of the company. Research done on the Airlines company sector were listed on the SkyTrax ranking for periods 2015 with purposive sampling technique and uses retrieved seven of the tan companies listed. This research uses descriptive quantitative research and use the documentation to collecting data. This research to made to fruition with details that the four companies are predicted to go bankrupt with unhealthy financial conditions, three companies predicted on a grey area or bankrupt-prone which allows this company into bankruptcy or could not bankruptcy due to the fluctuating financial conditions create ever encountered the unhealthy financial conditions financial conditions are prone. This research will support high-level accuracy by using the Z-Score model analysts by Altman.